One-year follow-up efects of the informed health choices secondary school intervention on students’ ability to think critically about health in Uganda: a cluster randomized trial - Ssenyonga, Ronald; Andrew, D. Oxman; Nakyejwe, Esther; Chesire, Faith; Mugisha, Michael; Nsangi, Allen; Matt, Oxman; Christopher, James Rose; Sarah, E. Rosenbaum; Jenny, Moberg; Kaseje, Margaret; Nyirazinyoye, Laetitia; et al. (Trials, 2025)
We assessed the effects of the Informed Health Choices (IHC) secondary school intervention on students’ ability to think critically about choices 1 year after the intervention. Methods We randomized eighty secondary schools to the intervention or control (usual curriculum). The schools were randomly selected from the central region of Uganda and included rural and urban, government, and privately-owned schools. One randomly selected class of year-2 students (ages 14–17) from each school participated in the trial. The intervention included a 2-day teacher training workshop, 10 lessons accessed online by teachers and delivered in classrooms during one school term (May–August 2022). The lessons addressed nine prioritized IHC concepts. We used two multiple-choice questions for each concept to evaluate the students’ ability to think critically about choices at both the end of the school term and again after 1 year. The primary outcome was the proportion of students with a passing score (≥ 9 of 18 questions answered correctly) on the “Critical Thinking about Health” (CTH) test. Results After 1-year, 71% (1749/2477) of the students in the intervention schools and 71% (1684/2376) of the students in the control schools completed the CTH test. In the intervention schools, 53% (934/1749) of students who completed the test had a passing score compared to 33% (557/1684) of students in the control schools (adjusted difference 22%, 95% CI 16–28). Conclusions The effect of the IHC secondary school intervention on students’ ability to assess health-related claims was largely sustained for at least 1 year.